BBAware - A Context-Aware Mobile and Wearable Architecture for Monitoring Beta-Blocked Cardiac Patients - da Silva, Alberto Vianna Dias; Vieira, Vaninha (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP); 2016: Anais do VIII Simpósio Brasileiro de Computação Ubíqua e PervasivaDO - 10.5753/sbcup.2016.9444, 2016)
Beta-blockade drugs are still in use as treatment option to lower heart rate, to improve cardiac function, and to reduce cardiovascular events. Patients who use beta-blockers usually surpass a therapeutic test full of collateral effects to adapt their organisms. Furthermore, these patients with a baseline heart rate above 70 beats per minute have a significantly higher risk of all cardiovascular events. Context-aware healthcare field arises as an alternative to monitor patients constantly. This paper introduces the Beta-Blocked Aware (BBAware) project, a pervasive solution, that uses the concepts of ubiquitous healthcare in order to help patients under beta-blockade treatments.